2019
DOI: 10.1186/s12891-019-3002-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between lifestyle and musculoskeletal pain: cross-sectional study among 10,000 adults from the general working population

Abstract: BackgroundWork-related musculoskeletal pain is a major cause of work disability and sickness absence. While pain is a multifactorial phenomenon being influenced by work as well as lifestyle, less is known about the association between specific lifestyle factors and the type of musculoskeletal pain. The aim of the study was to investigate if a dose-response association existed between lifestyle factors and musculoskeletal pain intensity in the low back and neck-shoulder.MethodsCurrently employed wage earners (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 58 publications
2
50
1
3
Order By: Relevance
“…The obtained data suggested that a history of smoking provided no statistically significant effect on the prevalence of musculoskeletal symptoms; however, descriptive analysis data revealed that this factor increased the prevalence of shoulders and lower back symptoms. Some previous researchers have reported the relation between smoking habits and MSDs [34,35]. The probable cause of the obtained result in our study was related to the low frequency (7%) of smokers in this study.…”
Section: Discussionsupporting
confidence: 41%
“…The obtained data suggested that a history of smoking provided no statistically significant effect on the prevalence of musculoskeletal symptoms; however, descriptive analysis data revealed that this factor increased the prevalence of shoulders and lower back symptoms. Some previous researchers have reported the relation between smoking habits and MSDs [34,35]. The probable cause of the obtained result in our study was related to the low frequency (7%) of smokers in this study.…”
Section: Discussionsupporting
confidence: 41%
“…In addition, the level of physical activity is associated with the risk of a community-acquired pneumonia in women, with pneumonia being a major complication of COVID-19 ( Baik et al, 2000 ). It is also known that greater physical activity is associated with a lower risk of musculoskeletal pain ( Kirsch Micheletti et al, 2019 ) and improves mental health issues, such as mood and depression, which is particularly relevant during social isolation ( Hammig et al, 2011 ; Cooney et al, 2013 ; McDowell et al, 2019 ; Denay et al, 2020 ; Meyer et al, 2020 ). Physical activity in fact has been shown to be similarly effective as psychological therapy and drug therapy in depression ( Cooney et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both smoking and second-hand smoke exposures were relatively common among fishermen, increasing the risk of smoking-associated health disorders, including musculoskeletal conditions. [35][36][37] Fishing generally requires continuous work for extended hours that may promote smoking. 20,38 A study in Washington State found significantly higher cigarette and marijuana smoking rates among fishers compared to the general population.…”
Section: Discussionmentioning
confidence: 99%